Controlled seeding density of nanodiamonds on silicon and its influence on diamond film adhesion - Zhicheng Xing; Stephan Handschuh-Wang; Tao Wang; Peigang Han; Bin He (Functional Diamond)
Several parameters are known to influence the adhesion of diamond coatings to non-diamond substrates. In the current work, we investigate the effect of seeding density on the adhesion of microcrystalline diamond coatings on silicon substrates. To this end, controlled seeding densities on silicon substrates were established by an electrostatic self-assembly seeding strategy. The seeding density was altered by changing the wt% of the ND colloidal seed solution while maintaining the pH and surfactant concentration. This resulted in colloidally stable ND particles with virtually constant hydrodynamic diameter (ca. 30 nm) and Zeta potential (ca. +32 mV) while the wt% of the ND in the colloid was altered between 0.00033 and 0.1 wt%. With these diluted solutions the seeding density was controlled between 4 × 108 cm−2 and 1.95 × 1011 cm−2. Subsequently, microcrystalline diamond coatings with a thickness of 3.1 ± 0.1 µm were grown. The adhesion of the diamond coating to the silicon substrate was evaluated by indentation. Best adhesion was found for a seeding density of 1.81 × 1011 cm−2, featuring no delamination and low sample to sample variation. Counterintuitively, further increase in seeding density resulted in an increase of crack length and sample to sample variation. This decline in adhesion was attributed to ND aggregates formed during the seeding step, which either desorb or form areas with poor diamond-silicon bonding upon diamond growth. Therefore, this result is of import for diamond film adhesion studies and commercial diamond coated cutting tools using high seeding densities being prone to aggregation.